2D High‐Entropy Transition Metal Dichalcogenides for Carbon Dioxide Electrocatalysis. Issue 31 (26th June 2021) - Cavin, John; Ahmadiparidari, Alireza; Majidi, Leily; Thind, Arashdeep Singh; Misal, Saurabh N.; Prajapati, Aditya; Hemmat, Zahra; Rastegar, Sina; Beukelman, Andrew; Singh, Meenesh R.; Unocic, Kinga A.; Salehi‐Khojin, Amin; et al.
Abstract: High‐entropy alloys combine multiple principal elements at a near equal fraction to form vast compositional spaces to achieve outstanding functionalities that are absent in alloys with one or two principal elements. Here, the prediction, synthesis, and multiscale characterization of 2D high‐entropy transition metal dichalcogenide (TMDC) alloys with four/five transition metals is reported. Of these, the electrochemical performance of a five‐component alloy with the highest configurational entropy, (MoWVNbTa)S2, is investigated for CO2 conversion to CO, revealing an excellent current density of 0.51 A cm −2 and a turnover frequency of 58.3 s −1 at ≈ −0.8 V versus reversible hydrogen electrode. First‐principles calculations show that the superior CO2 electroreduction is due to a multi‐site catalysis wherein the atomic‐scale disorder optimizes the rate‐limiting step of CO desorption by facilitating isolated transition metal edge sites with weak CO binding. 2D high‐entropy TMDC alloys provide a materials platform to design superior catalysts for many electrochemical systems. Abstract : High‐entropy transition metal dichalcogenide alloys containing 4 or 5 transition metals are synthesized based on first‐principles stability predictions. The 5‐component alloy (MoWVNbTa)S2 is shown to be an excellent electrocatalyst for the conversion of CO2 into CO. First‐principles calculations suggest that a small concentration of highly active sites is responsible for the high activity.